Osteochondral Allograft Transplantation: Identifying the Biomechanical Impact of Using Shorter Grafts and Pulsatile Lavage on Graft Stability. Issue 7 (29th July 2019) - Babu, Jacob; Hodax, Jonathan D.; Fadale, Paul D.; Owens, Brett D.
Objectives: This study seeks to identify the ability of shorter Osteochondral Allografts (OCAs) to resist displacement/failure. Additionally, this study seeks to evaluate the effect of pulsatile lavage on the biomechanical stability of the OCA graft. Methods: Fifteen millimeter diameter, human cadaveric, osteochondral allografts of 4 mm, 7 mm, and 10 mm in depth were harvested for comparison of resistance to compressive and tensile loads. For each group 7 specimens were subjected to tensile loads and 3 specimens subjected to compressive loads until failure (pull-out or subsidence). An additional study group of 10 pulsatile lavaged (PL) osteochondral allografts of 15 mm in diameter and 7 mm in depth were introduced for comparison to the original 7 mm depth OCA group. Results: The average tensile forces for failure for the 4 mm, 7 mm, and 10 mm plugs were 23.74 N, 199.57 N and 197.69 N respectively (p=1.5x10-5). After post-hoc analysis of the tensile groups, significant differences in the mean tensile force to failure were appreciated between the 4 mm and 7 mm groups (p=4.12 x10-5) and the 4 mm and 10 mm groups (p=1.78x10-5), but not between the 7 mm and 10 mm groups (p=.9601). There were no significant differences between the average tensile forces resulting in failure for the 7 mm and 7mm-PL groups (199.57 N and 205.2 N, p=.90) or compressive forces to failure respectively (733.6 N and 656 N, p=.7062). Conclusion: For OCAs of 15 mm in diameter, a commonly used size in practice, we recommend that plugs of 7 mm in depth be utilized. Pulsatile lavage of allografts prior to insertion does not appear to take away from the structural integrity and stability of the plug, however an adequately powered study should confirm this. With many described theoretical benefits of decreased immunogenicity and better long term graft incorporation after lavage, we recommend that this practice continue. Table 1. Failure Loads Tensile Force to Failure Plugs 4 mm (n=7) 7 mm (n=7) 10 mm (n=7) Average Force (N) 23.74285714 199.5714286 197.6857143 ANOVA p = 1.5x10 -5 Compressive Force to Failure Plugs 4 mm (n=3) 7 mm (n=3) 10 mm (n=3) Average Force (N) 911.2333333 733.6 760.3 ANOVA p = .802762 Post-Hoc analyses (t-test) p values after comparison for tensile tests 4mm 7mm 7mm 4.12x10 -5 10mm 1.78x10 -5 0.9601 Note: For ANOVA, significant p<.05. After Post-Hoc analysis, statistical significance defined as p<.0167 per the Bonferroni correction for 3 comparisons.